Mountain Bicycle Cycling Comfort on Different Road Surfaces - Soffarina Soffarina (Widyagama University of Malang, 2020)
Mountain bicycle is one of the types of bicycles, and it is made for off-road cycling. The main objective of the research is to focus on the surface of the road and weight to obtain and measure the vibration produce on the mountain bicycle. In order to investigate the vibrations, an accelerometer is placed under the saddle of the bicycle in order to get an accurate reading for different types of surfaces and the vibration of the weight. The cyclist had to cycle for 400 m in the average of 5.1 to 6.1 revolutions per minute on four different surfaces, and four different weight were investigated. The results show that the highest acceleration produced is which refers to mean value is the acceleration of loose gravel which is 0.46190. There is an insignificant value in the weight of the driver weighing 60 kg if replaced with 70 kg, 80 kg if the bike is running on four different kinds of roads.